ВЕРОВАНИЯ И ОБРЯДЫ КАРАКАЛПАКОВ, СВЯЗАННЫЕ С ПОЧИТАНИЕМ БАРАНА - Есбергенова, С.Х. (SCIENCE and SOCIETY, 2019)
This scientific article highlights the problem of studying ancient relics, beliefs, rites and cults of Karakalpaks, connected with the veneration of the ram, preserved in mythology and folklore, which have been kept until recently in the people. The form of veneration of the ram in the image of the spirits of patrons, zoomorphic features in the cult of ancestors were analyzed; The historical and cultural ties of Karakalpaks with other peoples have been explored to establish common patterns in the history of religious beliefs associated with honoring a ram by Karakalpaks.